583. Demographic Factors and Clinical Outcomes Associated with Mental Health Medication Use in People Living with HIV. (26th November 2018) - Mathur, Swati; Roberts-Toler, Carla; Tassiopoulos, Katherine; Goodkin, Karl; McLaughin, Mirena; Koletar, Susan; Erlandson, Kristine
Abstract: Background: Mental health (MH) conditions and pain are common among people living with HIV (PLWH). An understanding of factors associated with prescriptions for these conditions and clinical impact of the prescriptions may improve care of MH disorders in PLWH. Methods: The use of mental health/pain-related medications was examined among PLWH within the AIDS Clinical Trials Group A5322 (HAILO) study. Use of medications (any use and class) was compared by sex. Multivariable logistic models estimated the association between MH medications (any/none) with (i) insurance status and race/ethnicity and (ii) baseline and incident slow gait (>1 second/m) and neurocognitive impairment (NCI) over 4 years. Results: Of 1035 participants, the median age was 51. 81% were men, 30% black, and 20% Hispanic. Similar numbers of men (34%) and women (38%) were on MH medications ( P = 0.19).Women were more likely to be prescribed opioids (12% vs. 5%; P < 0.001); other classes were similar. In multivariable models, MH-medicated PLWH were more likely to have Medicare (odds ratio [OR] 2.50, 95% CI 1.50–4.16, P < 0.001) or public insurance (1.85; 1.23–2.78, P = 0.003) vs. no/unknown insurance; and less likely to be Hispanic vs. white (0.48; 0.33–0.69; P < 0.001). MH-medicated PLWH had greater odds of baseline slow gait (1.80; 1.34–2.40; P < 0.001). The sex-specific ORs for NCI were qualitatively different (men: 1.70; 1.09–2.66; women: 0.96; 0.43–2.18); but this difference was not significant in the multivariable model ( P interaction = 0.227). There was an increased risk of incident slow gait among MH-medicated men but not women (hazard ratio 1.74; 1.22–2.48 vs. 0.76; 0.38–1.52, P interaction = 0.038), and a trend toward increased risk of incident NCI (1.76; 0.91, 3.39, P = 0.09) for both sexes. Conclusion: Our results highlight socioeconomic and ethnic differences in prescription of MH medications. The higher proportion of opiate prescriptions among women needs confirmation and should be a priority for intervention. The greater risk of baseline NCI and incident slow gait among men may be the result of differences in toxicity, drug interactions, or persistent mental health symptoms; further investigation is needed to optimize outcomes in PLWH and prescription of mental health medications. Disclosures: All authors: No reported disclosures.